Mothers' expectations and other factors affecting breastfeeding at six months in Greece. (December 2013) - Bouras, Georgios; Mexi-Bourna, Panagioula; Bournas, Nicolaos; Christodoulou, Christos; Daskalaki, Anna; Tasiopoulou, Ioanna; Poulios, Antonios
The objective of this study is to determine the factors influencing breastfeeding duration in Greece. A total of 145 women were interviewed, on the third day post-partum. Women were followed up by telephone interviews at three and six months post-partum. Chi-square test and binomial sequential logistic regression analysis were used for statistical analysis. Results from this study show that baby-friendly hospital, antenatal courses, mother's perception of her capability to successfully breastfeed her infant, mother's intention to breastfeed for a duration of six months or more, mother's and father's education level, introduction of complementary foods or fluids, caesarean delivery, smoking and ethnicity were significantly associated with the duration of breastfeeding. In conclusion, additional antenatal and postnatal framework is necessary. Mothers' prediction of the duration of breastfeeding is an additional tool for identification of women with a high probability for early weaning.